CANAL CAPACITY IN AREA IKIP AND PULOMAS - Budi Satiawan; Puspita Maratus Sholeha (International Journal of Civil Engineering and Infrastructure, 2021)
IKIP’s Pump House is located on Inspeksi Kali Sunter street, North Jakarta, geographically located between 6°9'45.55" South Latitude and 106°52'53.8” East Longitude. While Pulomas’s Pump House is located on Perintis Kemerdekaan street North Jakarta, geographically located between 6 °10'0.71'' latitude and 106°52'51.66” east longitude. On the arterial road beside Ria-rio Reservoir to Kayu Putih street, floods often occur during the rainy season. That flood is caused by several factors, one of which is the drainage canal that can’t function properly. At several points of water canal that will lead to Pulomas’s Pump House there’s a lot of plastic waste and people's belongings that cause narrowing of canal. The high sedimentation in the form of mud also causes water capacity that can be accommodated by canal is not optimal. From the above conditions, it is necessary to do an analysis pump capacity to determine whether IKIP’s Pump House and Pulomas’s Pump House can still accommodate water discharge based on 15 years of rainfall lastly, and it is known that there are three canals in the Pulomas pump house that cannot accommodate the water discharge so that flooding occurs